Inactivation of Vhl in Osteochondral Progenitor Cells Causes High Bone Mass Phenotype and Protects Against Age‐Related Bone Loss in Adult Mice. (April 2014) - Weng, Tujun; Xie, Yangli; Huang, Junlan; Luo, Fengtao; Yi, Lingxian; He, Qifen; Chen, Di; Chen, Lin
ABSTRACT Previous studies have shown that disruption of von Hippel–Lindau gene (Vhl) coincides with activation of hypoxia‐inducible factor α (HIFα) signaling in bone cells and plays an important role in bone development, homeostasis, and regeneration. It is known that activation of HIF1α signaling in mature osteoblasts is central to the coupling between angiogenesis and bone formation. However, the precise mechanisms responsible for the coupling between skeletal angiogenesis and osteogenesis during bone remodeling are only partially elucidated. To evaluate the role of Vhl in bone homeostasis and the coupling between vascular physiology and bone, we generated mice lacking Vhl in osteochondral progenitor cells (referred to as Vhl cKO mice) at postnatal and adult stages in a tamoxifen‐inducible manner and changes in skeletal morphology were assessed by micro–computed tomography (µCT), histology, and bone histomorphometry. We found that mice with inactivation of Vhl in osteochondral progenitor cells at the postnatal stage largely phenocopied that of mice lacking Vhl in mature osteoblasts, developing striking and progressive accumulation of cancellous bone with increased microvascular density and bone formation. These were accompanied with a significant increase in osteoblast proliferation, upregulation of differentiation marker Runx2 and osteocalcin, and elevated expression of vascular endothelial growth factor (VEGF) and phosphorylation of Smad1/5/8. In addition, we found that Vhl deletion in osteochondral progenitor cells in adult bone protects mice from aging‐induced bone loss. Our data suggest that the VHL‐mediated signaling in osteochondral progenitor cells plays a critical role in bone remodeling at postnatal/adult stages through coupling osteogenesis and angiogenesis. © 2014 American Society for Bone and Mineral Research.